Decolonizing the Endowment: A Critical Framework for Restructuring Museum Financial Portfolios to Support Restitution and Equity in Indonesia - Yuniarti Maretha Pasaribu; Firzan Dahlan; Grace Freya Purba; Susi Diana; Giselle Dupont; Farah Faiza; Danila Adi Sanjaya (Enigma Institute, 2025)
Museums globally are facing a profound ethical reckoning with their colonial foundations. In Indonesia, a nation with a rich history of resisting colonial rule, this discourse has intensified calls for the restitution of cultural artifacts. However, a critical barrier to these decolonial ambitions lies within the financial architecture of museums themselves: the endowment. This study investigated how traditional museum endowment management, guided by principles of perpetuity and maximum growth, often conflicts with and obstructs the ethical imperatives of restitution and equity. This research employed an explanatory sequential mixed-methods design. Initially, a quantitative analysis of the investment portfolios of three representative Indonesian museums—a national museum, a private institution, and a regional museum—was conducted. This was followed by a qualitative phase involving in-depth, semi-structured interviews with 22 museum directors, curators, financial managers, and representatives from source communities. The data were analyzed to identify correlations between investment strategies and institutional capacities for decolonial action. The findings revealed that museum endowments were predominantly invested in global equity and bond markets, with significant exposure to multinational corporations in the Global North, including those in extractive and banking sectors with colonial entanglements. This structure created a